Sustainability of Groundwater for Irrigation Purposes in Semi-arid Parts of Namibia - Amwele, Hilma Rantilla; Kgabi, Nnenesi Anna; Kandjibi, Liisa Indileni (Frontiers in Water, 2021)
The groundwater quality data from 1,137 boreholes in 10 regions of Namibia were assessed for sodium adsorption ratio (SAR), Kelly's ratio (KR), sodium percentage (Na%), magnesium adsorption ratio (MAR), total hardness (TH), soluble sodium percentage (SSP), potential salinity (PS), electrical conductivity (EC), and total dissolved solids (TDS) to determine the suitability for the irrigation. The groundwater was classified as follows: all the regions' groundwater shows the TH as very hard water of >4.6 meq/l, PS as not suitable for irrigation (>3 meq/l), and EC as very highly (0.75–2.25 dS/m). However, Na%: 10% of regions have doubtful water (>80%), MAR: 30% of regions are not recommended for irrigation (>50 meq/l), and TDS: 90% of the regions have slightly moderate (450–2,000 mg/l) and 10% have groundwater that is unsuitable for agricultural purposes (>2,000 mg/l). The unsuitability of groundwater for irrigation could be due to higher concentrations of K+, Mg2+, Ca2+, and Cl− that has exceeded the FAO guideline for irrigation. Some groundwater qualities had inverse classification such as SAR all regions have excellent groundwater (<10 meq/l), KR: 90% of regions have safe water (<1 meq/l), Na%: 50% of regions have good groundwater (20–40%), 40% of the regions have permissible water (40–80%), and MAR: +70% of region's water is recommended for irrigation (<50 meq/l).